2014
DOI: 10.1037/a0033013
|View full text |Cite
|
Sign up to set email alerts
|

Awake/sleep cortisol levels and the development of posttraumatic stress disorder in injury patients with peritraumatic dissociation.

Abstract: Differences in the time of day that cortisol is sampled and failure to consider the impact of peritraumatic dissociation have been hypothesized as factors possibly contributing to the inconsistent findings in research examining associations between cortisol levels soon after trauma exposure and the subsequent development of posttraumatic stress disorder (PTSD). The present study examined associations between urinary cortisol levels during wake and sleep times soon after a serious injury and the subsequent deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In general, during periods of stress, cortisol dysregulation can be identified, which produces volumetric alterations in the brain, so the two biomarkers have negative correlations in patients with PTSD [24,67]. However, ironically, hypocortisolism was observed in patients with PTSD since it could be influenced by several causes including dissociative symptoms as we described [16,56,57]. Therefore, the relationship between cortisol and brain volume should be more discussed in further studies considering these points.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In general, during periods of stress, cortisol dysregulation can be identified, which produces volumetric alterations in the brain, so the two biomarkers have negative correlations in patients with PTSD [24,67]. However, ironically, hypocortisolism was observed in patients with PTSD since it could be influenced by several causes including dissociative symptoms as we described [16,56,57]. Therefore, the relationship between cortisol and brain volume should be more discussed in further studies considering these points.…”
Section: Discussionmentioning
confidence: 76%
“…Second, dissociative symptom, which were commonly observed in patient with PTSD, could a significant influencing factor of low cortisol level in patients with PTSD [ 16 ]. Previous studies reported that the dissociative subtype of PTSD exhibit a symptom like derealization or depersonalization, which could be attributed to low cortisol levels of patients with PTSD [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between cortisol levels and PTSD have been studied extensively but remain incompletely understood [ 11 , 12 ]. For example, urinary or salivary cortisol levels have been reported to be lower [ 13 , 14 ], higher [ 15 ], or not changed [ 16 ] in PTSD groups compared to control groups. The role of the hypothalamus in regulation of cortisol in PTSD patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These inconsistencies can be attributed not only to the methodological differences [ 4 ] but also heterogeneity within the PTSD group, including comorbid disorders [ 5 ], chronicity, types, and duration of the illness [ 2 ]. Further, emerging research has identified the divergent impact of the dissociative subtype of PTSD on cortisol levels [ 6 - 8 ]. The patients of this distinct PTSD subgroup exhibit an emotional detachment following traumatic events in the form of depersonalization or derealization [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The patients of this distinct PTSD subgroup exhibit an emotional detachment following traumatic events in the form of depersonalization or derealization [ 9 ]. Several studies have reported that patients with higher dissociation levels showed reduced blood cortisol levels when compared to those with lower dissociation levels [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%